The Effectiveness of Eco Enzymes to Suppress the Development of Sarcoptes scabiei Mites In Vitro - N. Ginting; P Patriani; Anwar; Mursyid, Tengku Alfian (Talenta Publisher, 2022)
Scabies is a disease caused by the mite Sarcoptes scabiei that attacks goats. It is quite difficult for traditional goat breeders to obtain scabies medicine because of the high price, so alternative treatment is necessary. This study aims to determine the effectiveness of eco-enzymes as an alternative for the treatment of scabies in goats. The study was conducted at the Sei Putih Goat Research Workshop, Galang District, from September to October 2021. This study used a factorial completely randomized design because there were two factors, namely the concentration of ecoenzymes (0%, 25%, 50%, 75%, 100%) and time difference (0 hours, 2 hours, 4 hours, 6 hours, 8 hours) and repeated 4 times. Each replication contained 10 mites. The parameters used were the number of dead mites, mite death rate and mite lethal concentration. The results showed that the ecoenzyme was effective in killing and suppressing the growth of Sarcoptes scabiei mites in vitro. The LC50 value is 40.45% which proves that the eco-enzyme is able to kill mites in goats.